Development of Computer-Based Instruction Based Learning Models in Electricity Transmission Engineering Lessons SMK Negeri 1 Precut Sei Tuan - Muhammad Iqbal Daulay; R. Mursid; Baharuddin Baharuddin (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
One of the formal education pathways that prepare its graduates to have excellence in the world of work is Vocational High Schools (SMK). Current problems in SMK are generally related to limited equipment, low practice costs, and a learning environment that is not suitable for the world of work. Education is carried out to achieve human resources with the ability to think which is formulated as "Higher Order Thinking Skills" (HOTS) which aims to form human resources with the ability to innovate and be able to solve problems. In developing CBI-based learning models, there are learning models that aim to provide a concrete learning experience through the creation of imitations of experiences that are closer to the actual atmosphere. Computer-based learning is strongly influenced by cognitive learning theory, a model of information processing that began to develop in the 60s and 70s.